Can habitat enhancement limit the ecological impacts of predatory fish stocking? An experimental approach - Gimenez Marie; Cucherousset Julien (Knowledge and Management of Aquatic Ecosystems, 2024)
Fish stocking is a ubiquitous management measure in freshwater fisheries but it can induce important ecological impacts on communities and recipient ecosystems. Habitat enhancement might limit the ecological impacts of fish stocking by directly supporting biodiversity and helping to maintain ecosystem functioning. In the present, we used a mesocosm experiment to assess whether habitat enhancement, through the addition of coarse woody habitat (CWH) in the form of thin branches bundled or within an iron cage, can limit the impact of stocking of a predatory fish, juvenile largemouth bass Micropterus nigricans, on prey communities and ecosystem functioning. Results demonstrated that, prior to stocking, there was overall no significant effect of habitat enhancement on zooplankton communities and a strong effect on benthic macroinvertebrate communities that was associated with a decrease in the decomposition rate of organic matter in mesocosms containing caged-CWH. We also found that the stocking of juvenile largemouth bass significantly affected the structure of zooplankton communities while we did not observe significant effects on macroinvertebrate communities and ecosystem functioning. This effect on zooplankton community structure was compensated by habitat enhancement, notably when using caged-CWH. This study showed that habitat enhancement alone may not be sufficient to compensate the potential effects of predatory fish stocking, and that the choice of materials used to enhance habitats is fundamental in driving the efficiency.